Enhancing fisheries education and research through the Canadian Fisheries Research Network: A student perspective on interdisciplinarity, collaboration and inclusivity - Katrine Turgeon; Sarah C.F. Hawkshaw; Kristin M. Dinning; Brady K. Quinn; Danielle N. Edwards; Catarina Wor; Courtenay E. Parlee; Allan Debertin; Mike Hawkshaw; Benjamin W. Nelson; Fan Zhang; Laura Benestan; et al. (Canadian Science Publishing, 2018)
Fisheries involve complex problems not easily addressed by a single discipline, methodology, or set of stakeholders. In 2010, the Canadian Fisheries Research Network (CFRN) was initiated to increase fisheries research capacity in Canada through interdisciplinary and inclusive research collaborations. As post-graduate students in the network, we reflected on the type of training necessary to tackle fisheries problems and reviewed opportunities available at Canadian universities to receive such training. This paper presents an overview of fisheries education currently available in Canada, reflects on our training within the CFRN, and proposes improvements to fisheries education and research. Our review of the subject revealed few dedicated fisheries programs, limited interdisciplinary programs, few specialized fisheries training programs, and a heavy reliance on academic supervisors to secure research opportunities in fisheries. In contrast, the CFRN enhanced our training by deliberately focusing on tools and techniques to address fisheries issues, providing venues to foster interdisciplinary and inclusive research collaborations, and exposing the realities of stakeholder collaborations. We call for post-graduate-level fisheries education and research that is interdisciplinary, collaborative, and inclusive to produce well-rounded scientists and managers, and we suggest ways that universities, researchers, and funding agencies can incorporate these themes into fisheries education and research.